Discharge Destination of Patients in Fast-Track Primary Hip and Knee Arthroplasty: Results From a Prospective Danish Cohort - Lyndrup, Oliver; Kehlet, Henrik; Jørgensen, Christoffer C.; Lindberg-Larsen, Martin; Jakobsen, Thomas; Gromov, Kirill; Andersen, Mikkel R.; Bieder, Manuel; Overgaard, Søren; Varnum, Claus (The Journal of arthroplasty, 2025)
Following the implementation of the fast-track protocol in total hip arthroplasty (THA), total knee arthroplasty (TKA), and unicompartmental knee arthroplasty (UKA), the median length of stay (LOS) has been significantly reduced without an increase in readmissions. However, it is unclear if the reduction in LOS is at the expense of an increase in nonhome discharge. The aim of this study was to investigate the discharge destination among THA, TKA, and UKA patients. The prospective multicenter study included 6,856 patients undergoing primary THA, TKA, and UKA in a fast-track setting with an overall median LOS of one day. Outcomes were discharge destination, median LOS in each discharge destination category, and cause of rehabilitation center discharge. Data were gathered using preoperative questionnaires and a review of medical records. Discharge destination and LOS were registered at discharge. We found that 99% of patients had been discharged to their own homes, of which 21% had been discharged to their own homes with home care. There were 1% who were discharged to a rehabilitation facility and 0.1% who were discharged to a nursing home. The THA (1%, 95% confidence interval [CI] 0.7 to 1) and TKA (1%, 95% CI 0.9 to 2) had a significantly higher rate of discharge to a rehabilitation facility compared to UKA (0.1%, 95% CI 0.0 to 0.5). Despite a short LOS, 99% of patients were discharged to their own homes. Rehabilitation facility discharge was only 1% and was mostly caused by inadequate postoperative mobilization.